STAT3 gene mutations and their association with pure red cell aplasia in large granular lymphocyte leukemia. Issue 3 (22nd January 2014) - Ishida, Fumihiro; Matsuda, Kazuyuki; Sekiguchi, Nodoka; Makishima, Hideki; Taira, Chiaki; Momose, Kayoko; Nishina, Sayaka; Senoo, Noriko; Sakai, Hitoshi; Ito, Toshiro; Kwong, Yok‐Lam
<x xml:space="preserve">Abstract</x> Large granular lymphocyte leukemia (LGL L) has been morphologically characterized as a group of lymphoproliferative diseases that include T‐cell large granular lymphocytic leukemia (T‐LGL L) and chronic lymphoproliferative disorders of natural killer cells (CLPD‐NK). We investigated mutations in the Src homology 2 (SH2) domain of the signal transducer and activator of transcription 3 (STAT3) gene in Asian cohorts of T‐LGL L and CLPD‐NK (n = 42 and 11, respectively). Two mutations, Y640F and D661Y, were identified using direct sequencing or allele‐specific (AS) PCR. Y640F and D661Y mutations were found in seven and 18 patients, respectively. Two patients were positive for both mutations. Frequencies of STAT3 mutations in T‐LGL L and CLPD‐NK were 47.6% and 27.2%, respectively. Pure red cell aplasia (PRCA) was associated with the mutations (P = 0.005). The mutations were persistently found at stable levels in some patients after more than 5 years using AS‐quantitative PCR. The results of the present study indicate that the SH2 domain of the STAT3 gene is frequently mutated in Asian T‐LGL L and CLPD‐NK, and that PRCA is closely correlated with the mutations.